Student Management to Produce Technology-Competencial Students Without Dependence - Muhammad Fahmi Fauzi; Nathanael Steven Roy Shah Putra Nababa; Tin Rustini (Journal of Future Education, 2024)
This research focuses on efforts to avoid learners' dependence on technology. The management of learners is able to overcome the dependence that can arise in them through several efforts such as directing learners to use technology properly. This research applies a research method in the form of Literature review. This research method means a research process by analyzing journals, books, and previous research related to the topic discussed. Technology has positive and negative sides depending on the individual who uses it. The positive side of technology is that it provides convenience for individual lives, but there are negative sides such as dependence and information distortion. This research produces efforts to overcome learner dependence based on the role of parents and teachers. Parents' efforts at home can include accompanying children and limiting technology time, and teachers can choose efforts such as fostering technology ethics and focusing technology devices only for learning purposes. Learner management efforts based on providing understanding of the positive and negative sides and limiting technology time are considered effective in avoiding learner dependence